IFN-γ-dependent NK cell activation is essential to metastasis suppression by engineered Salmonella - Qiubin Lin (Nature Portfolio, 2021)
Cancer metastasis is one of the major causes of cancer related deaths and there is an urgent need to find more clinically effective metastasis targeting agents. Here, the authors show that Salmonella YB1 inhibits metastasis in multiple mouse models of cancer through a mechanism dependent on IFN-γ and NK cells.